Dairy-derived ingredients food and nutraceutical uses - Corredig, Milena, 1967- (CRC Press ; Woodhead Pub., 2009)
Annotation Advances in technologies for the extraction and modification of valuable milk components have opened up new opportunities for the food and nutraceutical industries. New applications for dairy ingredients are also being found. Dairy-derived ingredients reviews the latest research in these dynamic areas. Part one covers modern approaches to the separation of dairy components and manufacture of dairy ingredients. Part two focuses on the significant area of the biological functionality of dairy components and their nutraceutical applications, with chapters on milk oligosaccharides, lactoferrin and the role of dairy in food intake and metabolic regulation, among other topics. The final part of the book surveys the technological functionality of dairy components and their applications in food and non-food products. Dairy ingredients and food flavour, applications in emulsions, nanoemulsions and nanoencapsulation, and value-added ingredients from lactose are among the topics covered. With its distinguished editor and international team of contributors, Dairy-derived ingredients is an essential guide to new developments for the dairy and nutraceutical industries, as well as researchers in these fields.
Keywords: Dairy products in human nutrition.; Functional foods.; Dairy processing.; elektronické knihy; electronic books